Implementation of minimum service standards in radiology installation of bhayangkara Semarang hospital - Rosidah, Siti; Jamil, Masfufatun; Utami, Lucky Restyanti Wahyu (Sean Institute, 2024)
Radiology as a means of support in making a diagnosis must be able to meet the minimum service standards of the hospital. According to Kepmenkes no. 129 of 2008 there are 4 indicators of Minimum Service Standards that must be met by radiology installations, namely: waiting time for thorax photos is not more than three hours, the executor is a radiology specialist, the damage of X-ray service failure in the form of photo damage ≤ 2%, customer satisfaction is set at ≥ 80%. These service standards must be carried out to maintain service quality and become a benchmark in performance assessment. This study aims to determine the procedures and results of the analysis of the implementation of Minimum Service Standards in the Radiology Installation of Bhayangkara Hospital. This type of research is qualitative. Data collection was carried out by means of observation, interviews with parties involved in the hospital quality assurance program and documentation of SPM program data that has been done.The data that has been obtained will be transcribed and reduced. Then the analysis will be carried out by referring to the SMP that has been determined by the hospital and the Kepmenkes. Furthermore, indicators that do not meet the standards will be evaluated in the hope that the quality assurance program can meet the standards. The results showed that the implementation of radiology minimum service standards at Bhayangkara Semarang Hospital has been carried out, including 4 indicators with the results meeting the standards, but processing and evaluation have not been carried out.